The Efficacy of Selected Insecticides Against Wheat Aphids on Irrigated Wheat in North Western Amhara, Ethiopia - Andualem, Mequanint; Asaye, Gebremariem (Department of Agronomy and Horticulture, IPB University, 2023)
Aphid infestations cause significant losses in wheat production. The experiment was conducted at the Koga irrigation site during 2021 to evaluate the efficacy of commercial insecticides for the management of wheat aphids. Seven types of insecticides with unsprayed control were laid in a completely randomized block design with three replications. The result showed a reduced aphid infestation with maximum grain yield were from dimethoate, imidacloprid, lambda-cyhalotrin, profenfos + lambda-cyhalothrin, imidacloprid + lambda-cyhalothrin, and profenofos-sprayed plots. However, the greater net benefit and marginal rate of return were provided by the applications of imidacloprid and dimethoate insecticides. The economically feasible insecticide application can be considered as an effective aphid management practice in wheat production.